Transparansi Pengelolaan Dana Musyawarah Desa Pertanggung Jawaban Tahunan (MDPT) Di Bumdesa Lancang Kuning Desa Rumbai Jaya - Nur Aisiyah Mulyati; Nuri Aslami; Nurlaila Nurlaila (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research is aimed at finding out the Transparency of Management of Annual Responsible Village Deliberation Funds (MDPT) in BUMDesa Lancang Kuning, Rumbai Jaya Village. By using a qualitative approach supported by descriptive methods. Data was collected by interviewing, observing and documenting. This research uses data collection techniques by interviewing directors and secretaries regarding financial reports. A series of studies produced conclusions showing that the Annual Accountability Village Deliberation Fund Management (MDPT) was in accordance with SAK ETAP with the percentage of completion method recognized in reports from 2019 to 2021. BUMDesa Lancang Kuning Rumbai Jaya Village was guided by SAK ETAP in preparing the report because it makes performance easier and can help minimize errors in recording reports, which has a beneficial impact on the progress of the entity. BUMDesa will continue to try to be the best for financial reporting.